2011
DOI: 10.1007/s10156-010-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and disease severity of healthcare-associated pneumonia among patients in a hospital in Kitakyushu, Japan

Abstract: Pseudomonas spp. and anaerobes were isolated from patients with HCAP than from those with CAP. Conversely, more Streptococcus pneumoniae was detected and more penicillin was used in patients with CAP. This study provides additional evidence that HCAP should be distinguished from CAP and suggests the pathogenesis and therapeutic strategy for HCAP may be similar to those of hospital-acquired pneumonia (HAP). Seki et al., Page 3 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…To our knowledge, several major studies have investigated the differences in the characteristics of patients with HCAP and CAP: four from Japan [11][12][13][14], two from the United States [3][4][5], and one each from the UK [7], Spain [15], Italy [16], and Korea [17]. To discuss the characteristics of patients with HCAP, it is important to compare the patient selection in each report, because insurance and can receive health care impartially, a distinctive characteristic of the reports from Japan.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, several major studies have investigated the differences in the characteristics of patients with HCAP and CAP: four from Japan [11][12][13][14], two from the United States [3][4][5], and one each from the UK [7], Spain [15], Italy [16], and Korea [17]. To discuss the characteristics of patients with HCAP, it is important to compare the patient selection in each report, because insurance and can receive health care impartially, a distinctive characteristic of the reports from Japan.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that HCAP is a heterogeneous disease and not all HCAP patients require a broad-spectrum multidrug regimen. Actually, several reports [10,13,[18][19][20] from Japan showed various values of frequency of MDR-pathogens and mortality rate of HCAP patients: frequency of MDR-pathogens was 3.3% to 42.9%; and mortality rate was 1.8% to 21.3%. In addition, the recent Japanese study [20] reported that the characteristics of HCAP patients are different between those admitted to large hospitals or small hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are diagnosed with NHCAP when they met at least one of the following criteria: (1) having been admitted to the long-term care hospital or nursing home; (2) discharge from hospital in the preceding 90 days; (3) elder or physically disability people who need care (ECOG PS score ≥3); (4) outpatients who receive infusion therapy (including dialysis, antibiotics, anticancer agent, and immunosuppressant drug). Complications were defined as described previously [9][10][11][12][13].…”
Section: Definitionsmentioning
confidence: 99%
“…Outbreaks in intensive care wards with bronchoscopes and transesophageal echocardiogram (TEE) probes were traced to damage to instruments and a lack of leak testing [18,42,43]. In the current ERCP-associated outbreaks minor defects were detected on the duodenoscopes at the distal end, on the outer sheath, on the elevator enclosure and on cover lenses, which were apparently not discovered during reprocessing or during use of the instruments, but only following the outbreak during servicing [19,20,21,22,23,24].…”
Section: Ensuring Reprocessing Quality and Infection Preventionmentioning
confidence: 99%